Liquid chromatography-tandem mass spectrometry determination of synthetic cathinones and phenethylamines in influent wastewater of eight European cities - Bade, Richard; Bijlsma, Lubertus; Sancho, Juan V.; Baz-Lomba, Jose A.; Castiglioni, Sara; Castrignanò, Erika; Causanilles, Ana; Gracia-Lor, Emma; Kasprzyk-Hordern, Barbara; Kinyua, Juliet; McCall, Ann-Kathrin; van Nuijs, Alexander L.N.; et al. (Chemosphere (Oxford), 2017)
The popularity of new psychoactive substances (NPS) has grown in recent years, with certain NPS commonly and preferentially consumed even following the introduction of preventative legislation. With the objective to improve the knowledge on the use of NPS, a rapid and very sensitive method was developed for the determination of ten priority NPS (N-ethylcathinone, methylenedioxypyrovalerone (MDPV), methylone, butylone, methedrone, mephedrone, naphyrone, 25-C-NBOMe, 25-I-NBOMe and 25-B-NBOMe) in influent wastewater. Sample clean-up and pre-concentration was made by off-line solid phase extraction (SPE) with Oasis MCX cartridges. Isotopically labelled internal standards were used to correct for matrix effects and potential SPE losses. Following chromatographic separation on a C18 column within 6 min, the compounds were measured by tandem mass spectrometry in positive ionization mode. The method was optimised and validated for all compounds. Limits of quantification were evaluated by spiking influent wastewater samples at 1 or 5 ng/L. An investigation into the stability of these compounds in influent wastewater was also performed, showing that, following acidification at pH 2, all compounds were relatively stable for up to 7 days. The method was then applied to influent wastewater samples from eight European countries, in which mephedrone, methylone and MDPV were detected. This work reveals that although NPS use is not as extensive as for classic illicit drugs, the application of a highly sensitive analytical procedure makes their detection in wastewater possible. The developed analytical methodology forms the basis of a subsequent model-based back-calculation of abuse rate in urban areas (i.e. wastewater-based epidemiology). [Display omitted] •A sensitive UHPLC-MS/MS method for the determination of ten NPS in wastewater.•In-sample stability was investigated at different pH and temperatures.•Matrix effects were accounted for using isotopically-labelled internal standards.•The fully validated methodology was applied to wastewater samples from around Europe.